EU Harmonisation of Norms Regulating Detention: Is EU Competence (Art. 82(2)b TFEU) Fit for Purpose? - Wieczorek, Irene (European journal on criminal policy and research, 2022)
The EU has acquired the competence to harmonise individual rights in the field of criminal procedure (Art. 82(2)b TFEU). This was hailed as a positive development helping redress the unbalance towards a too security-oriented development of the Area of Freedom Security and Justice. This article discusses the breath of this competence and designs an analytical framework illustrating what requirements need taking into account to legitimate EU regulatory action in the field of detention. It argues that the wording of the provision, especially its utilitarian framing, strongly limits its potential for the EU to act in at least two areas, compensation for unjust detention and material detention conditions.